On Non Inclusive Distance Vertex Irregularity Strength of Tadpole and Path Corona Path Graphs - Muhammad Bilal; Diari Indriati; Vika Yugi Kurniawan (Universitas Sebelas Maret, 2020)
Let ???? = (????, ????) be a connected and simple graph with vertex set ????(????) and edge set????(????). A non inclusive distance vertex irregular labeling of a graph ???? is a mapping of ???? ∶ (????, ????) → 1, 2, … , ???? such that the weights calculated for all vertices are distinct. The weight of a vertex ????, under labeling ????, denoted by ????????(????), is defined as the sum of the label of all vertices adjacent to ???? (distance 1 from ????). A non inclusive distance vertex irregularity strength of graph ????, denoted by ????????????(????), is the minimum value of the largest label ???? over all such non inclusive distance vertex irregular labeling. In this research, we determined ????????????(????) from ????????,???? graph with ???? ≥ 3, ???? odd, ???????????? ???? ≥ 1 and ???????? ⊙ ???????? graph ????????????ℎ ???? ≥ 2 and ???? even.